Heaven's Interpreters Women Writers and Religious Agency in Nineteenth-Century America - Reed, Ashley (Cornell University Press, 2020)
In Heaven's Interpreters, Ashley Reed reveals how nineteenth-century American women writers transformed the public sphere by using the imaginative power of fiction to craft new models of religious identity and agency. Women writers of the antebellum period, Reed contends, embraced theological concepts to gain access to the literary sphere, challenging the notion that theological discourse was exclusively oppressive and served to deny women their own voice. Attending to modes of being and believing in works by Augusta Jane Evans, Harriet Jacobs, Catharine Maria Sedgwick, Elizabeth Oakes Smith, Elizabeth Stoddard, Harriet Beecher Stowe, and Susan Warner, Reed illuminates how these writers infused the secular space of fiction with religious ideas and debates, imagining new possibilities for women's individual agency and collective action.Thanks to generous funding from Virginia Tech and its participation in TOME (Toward an Open Monograph Ecosystem), the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellopen.org) and other repositories.